The future of employment relations from the perspective of human resource management. (September 2014) - Boxall, Peter
This article defines 'human resources' as the overt talents and underlying characteristics that people possess, and identifies three agendas in human resource management: the individual, the organisational and the societal/global. The academic discipline of human resource management (HRM) has grown up around the second agenda: the needs of managers to hire, motivate and develop people with the talents that organisations need. Like the curate's egg, it is of variable quality: a tension between 'best-practicism' and analytical thinking is still present in it. Research in industrial relations has been more helpful in describing the spread of employer behaviour and analysing the reasons for it. However, the growing emphasis in academic HRM on understanding the psychological and social processes inside the 'black box' of the firm is encouraging the study of mutuality and sustainability in employment relationships. This direction has the potential to make academic HRM more relevant at the societal level where we confront issues of underutilisation and overutilisation of human resources and where we have a mix of human resource philosophies that both help and harm society. The challenge is to build a theory of how organisations can meet their needs for profit and renewal while supporting employee fulfilment and well-being over the long-run.